2021
DOI: 10.1111/dom.14311
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of mortality and major cardiovascular complications in type 2 diabetes: External validation of UK Prospective Diabetes Study outcomes model version 2 in two European observational cohorts

Abstract: Aim: To externally validate the UK Prospective Diabetes Study Outcomes Model version 2 (UKPDS-OM2) by comparing the predicted and observed outcomes in two European population-based cohorts of people with type 2 diabetes. Materials and methods: We used data from the Casale Monferrato Survey (CMS; n = 1931) and a subgroup of the Hoorn Diabetes Care System (DCS) cohort (n = 5188). The following outcomes were analysed: all-cause mortality, myocardial infarction (MI), ischaemic heart disease (IHD), stroke, and cong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…37 This may reflect earlier diagnosis of diabetes in ASCEND participants compared with participants in UKPDS and improved risk factor control in recent years. Given that the overprediction for death and MI is consistently observed in other validation studies, [17][18][19][20] this suggest that perhaps improvements in diabetes and CVD diagnosis and treatment and dietary and lifestyle changes have an impact on CV risks beyond the impact from risk factors accounted for by the UKPDS-OM2. Previous studies have also observed a decline in age-adjusted CVD incidence and case-fatality rates in the last 2 decades, 36,[38][39][40][41] over and above the effects explained by improvement in risk factors.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…37 This may reflect earlier diagnosis of diabetes in ASCEND participants compared with participants in UKPDS and improved risk factor control in recent years. Given that the overprediction for death and MI is consistently observed in other validation studies, [17][18][19][20] this suggest that perhaps improvements in diabetes and CVD diagnosis and treatment and dietary and lifestyle changes have an impact on CV risks beyond the impact from risk factors accounted for by the UKPDS-OM2. Previous studies have also observed a decline in age-adjusted CVD incidence and case-fatality rates in the last 2 decades, 36,[38][39][40][41] over and above the effects explained by improvement in risk factors.…”
Section: Discussionmentioning
confidence: 59%
“…External validations of the UKPDS-OM2 have been performed in several more recent North American cohorts, 17 , 18 a German cohort, 19 an Italian cohort and a Dutch cohort. 20 All studies report overprediction of mortality. This is consistent with observations in the report from the latest Mount Hood Diabetes Challenge, a forum for diabetes modelers to compare model performance, which found the UKPDS-OM2 and other diabetes model based on risk equations of the UKPDS-OM2 to overestimate cardiovascular (CV) mortality, although the results were generated using simulated patient cohorts instead of individual patient-level data.…”
Section: Introductionmentioning
confidence: 99%
“…This model has been validated in different populations, including Italy and Netherlands. [28] In a validation study using EXSCEL data, the model gave event rates that were similar to those observed but overestimated numbers of cardiovascular deaths and did not predict the reduction in all-cause mortality seen with EQW. [29]…”
Section: Discussionmentioning
confidence: 81%
“…This cost-effectiveness analysis was based on patient-level data for 14,752 patients followed up to 6.7 years, which makes it one of the largest samples for a within-trial economic evaluation of GLP-1 RA use in patients with established type 2 diabetes. [28] Trial outcomes were extrapolated using the UKPDS-OM2, [14] which uses data from a population of UK patients recruited between 1977 and 1991 and followed up until 2007. This model has been validated in different populations, including Italy and Netherlands.…”
Section: Discussionmentioning
confidence: 99%
“…The commitment to intensify the treatment not only of blood glucose, but also of associated comorbidities such as blood pressure, lipid profile, cigarette smoking and lifestyle undoubtedly contribute to improving cardiovascular prognosis, as also documented by other studies [61 -63]. It is not overlooked that even glycemic control alone brings significant benefits but that also the intensive control of other risk factors determines a better cardiovascular prognosis [61][62][63][64][65]. In addition, the comparative evaluation of subjects with and without lipohypertrophy adds new knowledge, clearly showing that the presence of LH describe a cluster of subjects with unsatisfactory glycemic control, large glycemic variability and an excess of hypoglycemic episodes, all factors increasing the already high cardiovascular risk.…”
Section: Discussionmentioning
confidence: 88%